Epidemiological study of paediatric germ cell tumours revealed the incidence and distribution that was expected, but a low mortality rate. (22nd February 2017) - Evers, Madeline; Rechnitzer, Catherine; Graem, Niels; Skov Wehner, Peder; Schroeder, Henrik; Rosthoej, Steen; Mosbech, Christiane Hammershaimb; Hoei‐Hansen, Christina Engel; Sehested, Astrid; Treger, Taryn D.; Brok, Jesper
Abstract: Aim: Germ cell tumours (GCTs) are a rare heterogeneous tumour group derived from primordial germ cells, which can be benign or malignant and occur in the gonads or extragonadally. This study mapped the paediatric GCTs in Denmark from 1984 to 2013 to study the incidence and outcome. Methods: We identified paediatric GCTs from the Danish Childhood Cancer and National Pathology Registries and reviewed the case records for patient characteristics, tumour characteristics and clinical outcome. Results: We identified 403 (71% female) paediatric GCTs and the crude incidence was 1.43 per 100 000. Of these, 79 (20%) were malignant, 39 (10%) were potentially malignant and 285 (70%) were benign. Extragonadal GCTs (39%) were mainly observed in early childhood and were predominately sacrococcygeal teratomas. Gonadal GCTs (61%) in late childhood were most frequently mature teratomas in the ovaries. Nearly all patients underwent surgery. Of the malignant tumours, 62% were treated with chemotherapy. Radiotherapy was only administered to intracranial GCTs. In the cohort, 12 patients died (3%). Conclusion: Paediatric GCTs in Denmark were mainly benign and mortality was low, even for malignant tumours. We identified a peak of extragonadal GCTs in early childhood and a peak of gonadal GCTs in late childhood, which was comparable to previous reports.